A critique of modernization and dependency theories in Africa: critical assessment - Matunhu, Jephias (Academic Journals, 2016)
The way states and development specialists rationalize how to commit economic resources to development is influenced, to a greater extent by their level of persuasion towards specific development theories. The discourse assesses the influence of modernization and dependency theories on Africa’s development. The conclusion is that both theories have failed to help develop Africa. The discourse pins hope on the African Renaissance theory of development.